Penerapan TAM Dalam Inovasi Pelayan Publik “Pak RT Suka Asik” Di Kabupaten Magetan - Agus Heru Maryanto; Sri Setyo Iriani; Sanaji Sanaji (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Digital transformation of public services is one of the targets of the Government in realizing good governance in the era of digitalization. The "PAK RT SUKA ASIK" application innovation is one of the many applications that make letter-writing services effective and efficient within the Magetan Regency. A study on public acceptance of technology is necessary to determine the suboptimal implementation of the government's public service innovation, the "PAK RT SUKA ASIK" application. The TAM 2 model was chosen to analyze and determine the factors that influence the intention to use the application in the Mranggen Village, Magetan District, Jawa Timur. A quantitative study with a cross-sectional design was conducted on respondent who had never used the application. The analysis results using SMART PLS 3.9.2 showed that the image variable is the only exogenous variable that affects the endogenous variable perceived of usefulness, in addition to the subjective norm variable that affects the image variable. The main factor causing the suboptimal implementation of the "PAK RT SUKA ASIK" application is the failure of socialization and evaluation of the use of the Village Government application, which results in the perceived usefulness and perceived ease of use of the "PAK RT SUKA ASIK" application not being felt by the community.